Issues selection of judges on the law of the Russian Federation. (Journal of actual problems of jurisprudence, 2016)
This article discusses qualification for judges under the laws of the Russian Federation. Author prepared a brief analysis of the current legislation of the Russian Federation regulating the issues of selection of judges . The necessity of increasing the requirements for the culture of behavior of law students . It is proposed to formalize it in law the concept of “ judicial career .” Based on the research also suggested to fix the Federal Law of the Russian Federation “On the Status of Judges “ rule mandating a candidate for judge of the degree of “ Master of Law “ , and that there is a long-felt need to raise the age limit for first-time applying for the post of judge .
Keywords: selection of judges; qualifications; training of judges; the judiciary; psychodiagnostic examination; the age limit